Value of the Ratio of Monocytes to Lymphocytes for Monitoring Tuberculosis Therapy. (27th May 2019) - Wang, Wei; Wang, Li-fei; Liu, Yan-yan; Yang, Fang; Zhu, Lei; Zhang, Xian-hui
Abstract : Objective . The objective of this study was to evaluate the change of the ratio of monocytes to lymphocytes in patients with active tuberculosis, such as to provide reference for clinical diagnosis and treatment. Methods . All data were collected from the clinical database of The Fifth People's Hospital of Taiyuan, China. A total of 151 patients who had newly diagnosed active tuberculosis with tuberculosis therapy in hospital and 129 healthy controls were selected. Results . Median ratio of monocytes to lymphocytes was 0.45 (IQR: 0.28–0.67) in patients before treatment and 0.32 (IQR: 0.25–0.46) on discharge (P < 0.001 ). Conclusions . Ratio of monocytes to lymphocytes may be applied in diagnosis and the chemotherapeutic efficacy of active tuberculosis.